2016
DOI: 10.1111/hsc.12351
|View full text |Cite
|
Sign up to set email alerts
|

Understanding eldercare users' views on quality of care and strategies for dealing with problems in Swedish home help services

Abstract: The aim of the present study was to gain a deeper understanding of eldercare users' strategies for dealing with problems in the quality of care and care satisfaction in relation to home help services. Based on earlier research and evaluations, it was assumed that users would express satisfaction and gratitude, and also be unwilling to complain. The specific research questions were: (i) What, if any, quality of care problems do the users mention? (ii) How do the users explain the reasons for these problems? and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Organisational support and time as identified by participants are intrinsically linked and impact on the environment within which health and aged care providers can establish and maintain rapport, thus enhancing the acceptability of services. Older people recognise how these affect the quality of care that is delivered [45]. The Thórarinsdóttir & Kristjánsson (2014) framework, mentioned above, purports that organisational values must recognise and embed respect and equity, key to active participation in care [27].…”
Section: Diversity Principles Underpin Care Participation Of Older Pementioning
confidence: 99%
“…Organisational support and time as identified by participants are intrinsically linked and impact on the environment within which health and aged care providers can establish and maintain rapport, thus enhancing the acceptability of services. Older people recognise how these affect the quality of care that is delivered [45]. The Thórarinsdóttir & Kristjánsson (2014) framework, mentioned above, purports that organisational values must recognise and embed respect and equity, key to active participation in care [27].…”
Section: Diversity Principles Underpin Care Participation Of Older Pementioning
confidence: 99%
“…These results are in line with previous studies; better leadership creates a better psychosocial work environment (Dellve, Skagert, & Vilhelmsson, 2007; Lundgren et al, 2015), and a better psychosocial work environment generates better recipient satisfaction in nursing homes (Dellve, Skagert, & Vilhelmsson, 2007; Lundgren et al, 2018). Previous research has also shown that leadership and psychosocial work environment have less impact on recipient satisfaction in home care compared with in nursing homes (Dellve, Skagert, & Vilhelmsson, 2007; Lundgren et al, 2018; Westerberg et al, 2017). Only one significant association was found in home care (between direct leadership and psychosocial work environment).…”
Section: Discussionmentioning
confidence: 96%
“…These interpersonal aspects are, according to Bishop et al (2008), important due to their indirect effects on nursing assistants. Westerberg, Hjelte, and Josefsson (2017) have noted that influence does not have an effect on recipient satisfaction in home care because recipients do not believe they are included in the decision-making process about their care. Regarding different aspects of the psychosocial work environment, more role conflict and exhaustion and less job satisfaction have been associated with low recipient satisfaction (Tzeng, Ketefian, & Redman, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Facility Evaluation Department of the SSIS abolished the settlement disclosure item, integrated the accounting management item, and repealed the document filing index in the scheme research to improve the social service QE system in 2019. In addition, it was improved so that it now measures the satisfaction of both consumers and suppliers by adding provided manpower satisfaction to user satisfaction [ 30 ].…”
Section: Discussionmentioning
confidence: 99%